2011
DOI: 10.1118/1.3666947
|View full text |Cite
|
Sign up to set email alerts
|

Antiscatter grids in mobile C-arm cone-beam CT: Effect on image quality and dose

Abstract: While grids improved CT number accuracy, soft-tissue CNR was reduced due to attenuation of primary radiation. CNR could be restored by increasing dose by factors of ~1.6-2.5 depending on GR, e.g., increase from 4.6 mGy for the thorax and 12.5 mGy for the abdomen without antiscatter grids to approximately 12 mGy and 30 mGy, respectively, with a high-GR grid. However, increasing the dose poses a significant impediment to repeat intraoperative CBCT and can cause the cumulative intraoperative dose to exceed that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Although the presence of a grid did not seem to improve the SNR in relation to applied radiation dose (Schafer et al, 2012), a significant decrease in cupping artefacts was observed (Kyriakou and Kalender, 2007). However, in certain high-scatter conditions, the grid could lead to a reduction in dose of up to 50% (Kyriakou and Kalender, 2007).…”
Section: Anti-scatter Gridmentioning
confidence: 84%
“…Although the presence of a grid did not seem to improve the SNR in relation to applied radiation dose (Schafer et al, 2012), a significant decrease in cupping artefacts was observed (Kyriakou and Kalender, 2007). However, in certain high-scatter conditions, the grid could lead to a reduction in dose of up to 50% (Kyriakou and Kalender, 2007).…”
Section: Anti-scatter Gridmentioning
confidence: 84%
“…Although scatter was fairly low due to the extended geometry (Schafer et al 2012), incorporation of scatter-correction as well as beam-hardening correction methods is the subject of ongoing work, with image quality from both analytic and iterative reconstruction methods expected to improve. Furthermore, statistical reconstruction methods have been adapted to include an electronic noise model (La Rivière and Billmire 2005, Xu and Tsui 2009), which may play an important role for improving image quality in the ultra-low dose regime.…”
Section: Discussionmentioning
confidence: 99%
“…In breast imaging, Kwan et al 43 measured ∼50% SPR at the detector for an average-size breast (14 cm diameter) and showed the benefit of a bowtie filter in reducing scatter. For mobile C-arm imaging, Schafer et al 44 showed that an antiscatter grid did not offer an improvement in CNR per unit square root dose. Similarly, Kyriakou et al 45 found that for low-to medium-scatter levels in C-arm CT, an increase in x-ray exposure was needed to compensate for primary absorption in the grid.…”
Section: Introductionmentioning
confidence: 99%